Obstructive sleep apnoea as a risk factor for osteopenia and osteoporosis in the male population. Issue 3 (7th January 2016) - Liguori, Claudio; Mercuri, Nicola Biagio; Izzi, Francesca; Romigi, Andrea; Cordella, Alberto; Piccirilli, Eleonora; Viola, Salvatore; Costa, Silvio; Sbraccia, Paolo; Marciani, Maria Grazia; Tarantino, Umberto; Placidi, Fabio
Obstructive sleep apnoea (OSA) is a sleep disorder characterised by recurrent apnoea events leading to hypoxia, hypercapnia and sleep disruption [1]. OSA represents a growing health problem mainly affecting men; in fact, its prevalence in the adult male population is between 4% and 24% [1–3]. This report proposes the clinical potential of monitoring bone mineral density in male OSA patients http://ow.ly/Voe47